Legal and Ethical Debate on Escorts on Public Roads: A Comparative Case Study - Sebastian, Muhammad vino; Akmala, Ali Faza; Torin, Muhammad Farrel Arrizky; Soegiarto, Ronald Christyanto (Dinasti Research, 2026)
Abstract: This research provides an extensive inquiry into the systemic conflict between judicial mandates and administrative finality within the Indonesian electoral justice system. By focusing on the high-profile disqualification and subsequent legal reinstatement of DPD candidate Irman Gusman, this study dissects the implementation of the principle of legal certainty (asas kepastian hukum) amidst the rigid progression of election stages. Using a normative-juridical framework, the paper evaluates the Jakarta State Administrative Court’s (PTUN Jakarta) findings regarding procedural maladministration and substantive misinterpretations of criminal law by the General Election Commission (KPU). Furthermore, it explores the broader implications of institutional resistance, where the KPU utilized the